ANALISIS PERJANJIAN CLOUD TERHADAP POTENSI PERANG SIBER DARI PERSPEKTIF ASAS KEPENTINGAN MILITER - Alessandro Praputranto; Jun Justinar (terAs Law Review : Jurnal Hukum Humaniter dan HAM, 2022)
The agreement program between the countries dubbed the cloud act was followed by the UnitedStates of America along with Northern Ireland and the United Kingdom. This agreement regulatesthe obligations of member countries of this multilateral agreement to comply with theirobligations to store, back up, or disclose their electronic data regardless of where the informationis located. From here it can be seen that there will be a "merging of member country data in aserver known as a cloud computing system." Later, the data from these member countries willbe stored in a cloud-based server so that it can facilitate accessibility, mobility, and portability.It is not meant that country data will be merged, but this is intended to provide special accessfor the United States to be able to access country data without the need for a warrant. Thenfrom the agreement, which will open up the privacy of its member countries, there will be prosand cons and various kinds of threats to security and defense from countries that are membersof the agreement. Thus, an analysis of the use of humanitarian law is needed in this cloud actagreement